FLOUTING AND HEDGING MAXIMS IN BBC PODCAST THE ENGLISH WE SPEAK TAKEN FROM BBC LEARNING ENGLISH - MANGARE, PRAISYA JOVANI KIENDY (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study uncovers how flouting maxim and hedging maxim are employed by the speakers in BBC Podcast The English We Speak from BBC Learning English. These scripts talk about daily phrases covering a broad range of factual matters which are used for communication. There are three problems of this study: (1) what types of maxims are flouted in the utterances found in the BBC Podcast The English We Speak scripts? (2) what types of maxims are hedged in the utterances found in the BBC Podcast The English We Speak scripts? (3) how the maxims are flouted and hedged in the utterances in the BBC Podcast The English We Speak scripts? It utilizes qualitative approach and document analysis. The result of analysis can be seen as follows: First, there are 37 utterances containing flouting maxims, which maxim of quantity takes the dominance as shown in 17 utterances. The speakers benefit from rhetorical strategies, such as irony, metaphor, tautology, overstatement and understatement to communicate the implied meaning. Second, 120 utterances of hedging maxims are found. Most speakers express uncertainty and inexactitude regarding the truth or their utterances so that hedges are used to avoid breaking the maxim also to minimize the imposition that may occur.  As a result, 74 utterances are said to hedge the maxim of quality. Overlapping incidence between flouting and hedging maxims also can be found referring that the speaker hopes the listener to interpret the meaning and to feel the speaker’s hesitation all at once so that a proper response can be derived. These findings suggest that flouting maxim is used when the speaker blatantly exploits the utterances based on a listener’s assumption. Besides, hedges are used to show that the speaker is still cooperative engaging in conversation, and as a way to opt out of conversational maxims. It is suggested that the next researchers to do deeper study and analysis in connection with cooperative principle and to apply various theories about maxim in conversation, such as politeness maxims. Keywords: Cooperative Principle, Flouting Maxims, Hedging Maxims, BBC Podcast The English We Speak